Three-Body Dispersion Coefficients for Excited Hydrogen Atoms (Journal of Atomic and Molecular Sciences, 2011)
The three-body van der Waals dispersion coefficients $Z(l_1l_2l_2)$ (up to $l_i = 5$) for the $H(1s)-H(1s)-H(1s)$ and $H(2s)-H(2s)-H(2s)$ systems are calculated by virtue of the dynamic polarizabilities at imaginary photon frequencies. The expression for the $2^l$-pole dynamic polarizabilities of atomic hydrogen is derived by application of the integration properties of the one-dimensional radial Coulomb Green's function. The results for the $H(1s)-H(1s)-H(1s)$ system are consistent with previous calculation in the literature, while the results for the $H(2s)-H(2s)-H(2s)$ systems are reported for the first time, and they are the main contribution of this work.